THE PROBLEM OF GENRE DIFFUSION IN THE LITERARY AND CRITICAL RECEPTION OF THE UKRAINIAN AND FOREIGN RESEARCHERS - Голод, Н. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the review of the historical and theoretic literary study works of the Ukrainian and foreign researchers, focused on the problem of genre diffusion in generics. The observation of the main approaches to the problem of studying “hybrid genres” is made. The reasons for the intensification of the genre synthesis process are analyzed in the historical literary development. The literary studies researchers’ views of the concept and category apparatus are generalized. The criteria of differentiation and the principles of systematization of the modified genres in the paradigm of the modern generics are determined.